2018
DOI: 10.19082/6430
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of combination of Viola odorata, Rosa damascena and Coriandrum sativum in prevention of migraine attacks: a randomized, double blind, placebo- controlled clinical trial

Abstract: BackgroundMigraine is the second most common type of headache after tension headaches. In Iranian traditional medicine several herbal drugs are used for the treatment of headache. Including, a product of Iranian traditional medicine, a combination of Viola odorata L. flowers, Rosa damascena L. flowers and Coriandrum sativum L. fruits.ObjectiveTo determine the effectiveness of a combination of Viola odorata flowers, Rosa damascene flowers and Coriandrum sativum fruits on severity, duration and frequency of migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…According to the results, the capsules alleviated Pharmaceutical Sciences (Indexed in ISI and Scopus) https://ps.tbzmed.ac.ir headache in patients with migraine. 47 In another clinical trial, ethanolic extract (400 mg capsules) of R. damascena had analgesic and anti-inflammatory effects and reduced postoperative pain. 48 The effects of R. damascena on pain relief have been presented in Table 5.…”
Section: Analgesic Effectsmentioning
confidence: 99%
“…According to the results, the capsules alleviated Pharmaceutical Sciences (Indexed in ISI and Scopus) https://ps.tbzmed.ac.ir headache in patients with migraine. 47 In another clinical trial, ethanolic extract (400 mg capsules) of R. damascena had analgesic and anti-inflammatory effects and reduced postoperative pain. 48 The effects of R. damascena on pain relief have been presented in Table 5.…”
Section: Analgesic Effectsmentioning
confidence: 99%
“…Apart from the leaves of C. sativum, the fruits may also have considerable effects on the migraine attacks (Kasmaei et al, 2016). The fruits of C. sativum in combination with the extracts of flowers of Viola odorata (commonly called wood violet or sweet violet belonging to Violaceae family) and Rosa damascena (commonly called damask rose, a hybrid variety) have a crucial role in controlling the pain in migraine patients (Kamali et al, 2018). From the available literature, it may be observed that, only very few studies have been conducted on the effects of extracts of C. sativum in the migraine patients and all the studies have reported positive effects on the control and management of migraine by the extracts of leaves, stem and fruits of C. sativum.…”
Section: Sa Vum and Migrainementioning
confidence: 99%